Asymptotic stability of solutions of systems of stochastic differential equations in the critical case - Yurchenko, I. V.; Yasinskaya, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We consider the problem of mean square stability and instability of trivial solutions of systems of stochastic differential equations with random operators in the critical case.